Promoting College Student’s Twenty-First Century Skills through a STEM Learning Project - Rifaatul Muthmainnah; Diah Ika Putri; Wina Fitriyani (Universitas Lampung, 2023)
There is a need to prepare college students with non-cognitive or 21st Century skills to prepare them for successful college and future careers. As the number of applied STEM in Indonesian education increases, research is needed to understand how STEM learning projects promote student 21st Century skills. This study used a case study and mixed-methods conversion design to convert qualitative data into quantitative data by applying pre-established rubrics. This study provides evidence that STEM learning projects are beneficial to promote students' 21st Century skills, which are: (a) knowledge construction, (b) real-world problem solving, (c) skilled communication, (d) collaboration, and (e) self-regulation. The result shows that students demonstrate the highest grade on collaboration and the lowest on knowledge construction. Although most of the student work introduced multiple 21st Century skills and the overall scores were satisfactory, student knowledge construction still needs improvement.Â DOI: http://dx.doi.org/10.23960/jbt.v11.i1.27046